Faktory uspešnogo i konfliktnogo obŝeniâ v usloviâh kulʹturno-stilevogo raznoobraziâ na materiale in internet-kommunikacii - Černyšova, Tatʹâna V. (Stylistyka, 2019)
The article presents the results of a comparative study of two types of public speech communication – of the official (media texts) and informal (social network) – in identifying their cultural and stylistic originality, and describes a set of linguistic and non-linguistic factors which are shaping the stylistic tone of the conflicting verbal interaction of participants of social networks. The object of study is the set (or sequence) of speech acts participants communications which was embodied in the text, allowing to trace the process of verbal interaction and its stages, favour or impede successful communication, i.e. implementation of authorial intention. As a tool of stylistic analysis the category of the “usual-style complex” is used. It is seen as a stylistic mechanism of selection, which allows us to describe the “real language of real era” with the given extra linguistic factors – namely, the context of the situation in which the interaction of participants of public communication occurs. The study concluded: despite the fact that the texts of formal and informal communication (media and social networks) have much in common, evaluation comments in social media are more specific, opponents are expressing their point of view and their promptings designed for the addressee: anger, accusations, refusal communication, etc. in the straightforward way. There are a lot of varieties of means and ways of expression – both verbal and nonverbal. Cultural and social skills of verbal communication play an important role in conditions of formal and informal public communication.